2005
DOI: 10.1037/0022-006x.73.6.1045
|View full text |Cite
|
Sign up to set email alerts
|

Social Information-Processing Skills Training to Promote Social Competence and Prevent Aggressive Behavior in the Third Grades.

Abstract: This article describes a school-based study designed to promote social competence and reduce aggressive behavior by strengthening children's skills in processing social information and regulating emotions. Three successive cohorts of 3rd graders (N = 548) from 2 schools participated. In 2000-2001, children received a routine health curriculum; in 2001-2002, students received the Making Choices: Social Problem Solving Skills for Children (MC) program; and in 2002-2003, children received MC supplemented with tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
105
0
14

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(127 citation statements)
references
References 64 publications
8
105
0
14
Order By: Relevance
“…The combination of two programs influenced on decreasing aggression and peer acceptance of children [15]. Moreover, in consonance with the outcomes of this study, another study examined the effects of Making Choices program and Making Choices program with the strong families program for parents on elementary school-age children and indicated of differences among children in interpreting of social cues in social situations without hostile, setting prosocial goals for themselves, and generate responses [46].…”
Section: Discussionmentioning
confidence: 89%
“…The combination of two programs influenced on decreasing aggression and peer acceptance of children [15]. Moreover, in consonance with the outcomes of this study, another study examined the effects of Making Choices program and Making Choices program with the strong families program for parents on elementary school-age children and indicated of differences among children in interpreting of social cues in social situations without hostile, setting prosocial goals for themselves, and generate responses [46].…”
Section: Discussionmentioning
confidence: 89%
“…encoding, mental representation, response accessing, evaluation and enactment, to these children can alleviate their behavioral problems, enhance their social interactions and help them direct their behavior. Frieser et al [10] also found the learning of social information processing skills to help improve the social competence and prevent aggression in children. In other words, thanks to these trainings, children with behavioral disorders are enabled to internalize their behavior, which acts as a self-control point of reliance.…”
Section: Discussionmentioning
confidence: 99%
“…The applications of this model include preventing reactive aggression in children [8], the defects of social information processing in adolescents subject to severe aggression [9], enhancing social competencies and preventing aggressive behaviors [10], coping strategies in aggressive, secluded and shy children [6], predicting behavioral extroversion problems [11], predicting cardiovascular activities in antisocial adolescent behaviors [12], mistreatment of the original family and symptoms of PTSD [13] and intergenerational aggression transmission [14]. Owing to their defective cognitive and social processing in problematic situations, children with behavioral problems suffer from contradictory reactions compared to normal children.…”
Section: Discussionmentioning
confidence: 99%
“…As stressed by some authors, 17,18 the systemic work related to gradual development of the ability to solve social problems has proven to be efficient for the treatment of aggressiveness in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%